Simulation Test Platform of Ｒoad Conditions for Electric Vehicle - ZHOU Mei-lan; ZHANG Xiao-ming; LIU Zhan-hua; ZHANG Yu (Journal of Harbin University of Science and Technology)
Aiming at the problem of simulating road conditions of the electric vehicle，a test platform is set up to simulate the road conditions of the electric vehicle. The simulation test platform adopts the towed mode to simulate the road conditions of the electric vehicle. Bidirectional electric dynamometer is used for loading motor. The platform uses two separate controllers to achieve the control of the motor， relying on host computer to send the relevant control commands to the controller to simulate the actual driving road conditions of the electric vehicle. Test platform not only can meet the steady-state testing requirements of the motor but also can complete the test of the transient and continuous cycling road. The test shows that the experimental results are all in the allowable error range compared with the theoretical results. The response time of testing platform is faster and the energy utilization rate also reaches more than 80% indicating that the platform achieve the requirements of the simulation test and energy saving effect of the test platform is also very obvious